Aberconwy House
As the great hall went out of use, except for large gatherings, newer houses were built with parlors. Where the great hall already existed, an extra floor was added above it to increase the number of rooms. The fireplace became an important part of every parlor but an attempt at insulation was made by covering the inside of the stone walls with plasterwork or timber paneling.